Design and Fabrication of Two-Filter Nano SL Mask to Deal with Covid-19 - Pashaie, Sajjad; Fisne, Mucahit; Habibpour, Romina (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: These days, due to the spread of infectious diseases such as COVID-19 and influenza, as well as the increase in air pollutants, the use of a face mask has become a necessity. Methodology: The technical field of invention is in the field of medical-health engineering. The present mask consists of 3 layers: from outside to inside, including Nano silk fabric, movable filter for peppermint essential oil (PEO)and silk cotton fabric, it makes COVID-19 disappear. Results: The use of a replaceable filter in the construction of the mask makes it washable and replaceable if contaminated, while re-washing existing masks to reuse them is incorrect; Because of the opening of the fibers in the mask and also changes in the physical and chemical structure, the mask loses its effectiveness and will have severe viral or microbial contamination. The use of a PEOfilter in the construction of the mask has an effective role in treating pneumonia, strengthening the immune system and disinfecting. Also, the layers of the mask are new compared to the existing masks, especially in the adhesive part of the layers and its connections, and their impermeability to the virus is innovative and inventive. Conclusion: By using this product, it is possible to take a big step in preventing COVID-19 and also to help move the economic wheels of the country. By implementing this plan, we can find a criterion for a suitable mask that for the first time the quality of the fabric mask is important in terms of filter interchangeability, wash ability, leakage and its filtering efficiency in the country. Key Words:COVID-19, PEO, Filter, Mask.